Novel Peptide NT/K-CFY Derived from Kringle Structure of Neurotrypsin Inhibits Neovascularization. (3rd October 2021) - Yao, Xieyi; Chen, Chong; Zhang, Jian; Xu, Yupeng; Xiong, Shuyu; Gu, Qing; Xu, Xun; Suo, Yan
ABSTRACT: Purpose : To assess the anti-neovascularization effect of a novel peptide NT/K-CFY derived from the kringle domain of neurotrypsin. Materials and Methods : Cell migration, lumen formation and cell proliferation assays were performed to determine the anti-neovascularization effect of NT/K-CFY in primary human umbilical vein endothelial cells (HUVECs). Chick chorioallantoic membrane (CAM) and oxygen-induced retinopathy (OIR) models were established to assess the anti-angiogenic role of NT/K-CFY in vivo . The retinal expression of vascular endothelial growth factor (VEGF) and pigment epithelium-derived factor (PEDF) was examined by western blot and real-time PCR in OIR model. Results : The in vitro results showed that NT/K-CFY effectively and safely decreased VEGF-induced cell migration, cell proliferation and tube formation in HUVECs. In addition, NT/K-CFY showed certain efficacy in angiogenesis inhibition in chicken embryos and oxygen-treated mouse pups. Moreover, the CFY peptide also improved retinal blood perfusion and reversed the abnormal expression of VEGF and PEDF in OIR mouse model. Conclusion : NT/K-CFY peptide strongly inhibits neovascularization in vitro and vivo . This novel peptide may become a promising therapeutic agent for ocular angiogenesis-related diseases.